2011
DOI: 10.3989/tp.2011.11056
|View full text |Cite
|
Sign up to set email alerts
|

Datación por <i>ESR</i> del yacimiento arqueológico del Pleistoceno inferior de Vallparadís (Terrassa, Cataluña, España)

Abstract: Excavated between 2005 and 2007, the site of Vallparadís (Terrassa, Spain) has given an abundant and diversified fauna associated with a rich Mode 1 industry. In order to complete the chronostratigraphic framework, we performed ESR and combined US-ESR dating applied to quartz grains extracted from sediments and fossil teeth, respectively. The results obtained are very significant, giving a weighted mean ESR age of 0.83 ± 0.13 Ma (2σ) for the reference archaeological level of the site (level 10) and another of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 55 publications
6
32
0
5
Order By: Relevance
“…In their article, they question the human occupation of Vallparadís during the Early Pleistocene. As we have shown in previous papers Duval et al, 2011;Garcia et al, 2011a, b): 1) a lithic set attributed to the Mode 1 has been found at the site; 2) associated with this set are bone remains with cutmarks and anthropogenic fractures; 3) the vertical distribution of the fossil record at EVT7 (levels 10 and 10c) presents three differentiated accumulations of material, which suggests there could have been several episodes of sedimentation and which, along with the identification of four direct lithic refittings, may indicate that part of the record was in primary position; 4) the presence of lithic industry at different levels throughout the stratigraphic sequence suggests continued human occupation; and 5) the radiometric (ESR-U/Series) and paleomagnetic datings, and the biochronological data place the sequence and the different levels with lithic industry at between 1.07 (lower limit of the Jaramillo subchron) and 0.6 Ma Martínez et al, 2010;Duval et al, 2011) (Fig. 1).…”
Section: Introductionsupporting
confidence: 52%
“…In their article, they question the human occupation of Vallparadís during the Early Pleistocene. As we have shown in previous papers Duval et al, 2011;Garcia et al, 2011a, b): 1) a lithic set attributed to the Mode 1 has been found at the site; 2) associated with this set are bone remains with cutmarks and anthropogenic fractures; 3) the vertical distribution of the fossil record at EVT7 (levels 10 and 10c) presents three differentiated accumulations of material, which suggests there could have been several episodes of sedimentation and which, along with the identification of four direct lithic refittings, may indicate that part of the record was in primary position; 4) the presence of lithic industry at different levels throughout the stratigraphic sequence suggests continued human occupation; and 5) the radiometric (ESR-U/Series) and paleomagnetic datings, and the biochronological data place the sequence and the different levels with lithic industry at between 1.07 (lower limit of the Jaramillo subchron) and 0.6 Ma Martínez et al, 2010;Duval et al, 2011) (Fig. 1).…”
Section: Introductionsupporting
confidence: 52%
“…4), as it had already been noted for Middle Pleistocene samples by Duval (2012). This phenomenon has been described for other dated materials such as tooth enamel , and the use of another function corresponding to the sum of a SSE function and a linear term (E+L) was proposed for teeth then for quartz (Duval et al, 2011;Moreno, 2011;Cordier et al, 2012 andDuval, 2012), considering that the global ESR signal is the result of the presence of two components in the Al signal:…”
Section: Dose Response Of Al-center In Quartzmentioning
confidence: 99%
“…Ages calculated using this new equation have been recently published for quartz of Lower Pleistocene and Middle Pleistocene ages (Duval et al 2011;Moreno, 2011;Cordier et al, 2012;Duval, 2012). The use of this equation has brought better accuracy for these ages and their use to date more recent sediments seems possible.…”
Section: Dose Response Of Al-center In Quartzmentioning
confidence: 99%
See 1 more Smart Citation
“…1B). Radiometric dating yielded an estimated age of 0.83 ± 0.07 Ma (Duval et al, 2011). Twenty-eight fossil mammal taxa were identified from layer EVT7, and show a predominance of typically Late Villafranchian species coupled with several new immigrants typically recorded from European Galerian associations (Madurell-Malapeira et al, 2010; Referred Specimens-EVT22049, partial right hemimandible with p3, m1, and m2 ( Fig.…”
Section: Age and Geologic Settingmentioning
confidence: 99%